IMPACT OF EXPORTS ON ALGERIA’S BALANCE OF TRADE STANDARD STUDY 1991-2021 - Mekkaoui , Mohammed; Elhachemi Hadjadj , Mohamed; Kouici , Mohamed (The journal of contemporary issues in business and government, 2023)
This study aims to illustrate the impact of exports on the Algerian trade balance for the period 1991-2021, using Johansson cointegration method, Granger causality test, and estimating the relationship according to the normal micro-square method. The study revealed the existence of a long-term balance between the trade balance and exports, inflation and oil prices, and a lack of causal correlation between them in both directions, with a correlation between exports, oil prices and the trade balance; however, there is an inverse relationship between inflation and the trade balance which is consistent with the economic theories.